P110 External ventricular drain-related infections: a single centre study. Issue 3 (14th February 2019) - Duddy, JC; O'Sullivan, MGJ; Lim, C; Kaar, GF
Abstract : Objectives: To quantify the External Ventricular Drain-related infection (ERI) rate in a one year period at Cork University Hospital, and to identify any risk factors for infection. Design: A retrospective audit of all External Ventricular Drains (EVDs) inserted in a one year period. Subjects: All patients who had an EVD inserted between February 2017 and February 2018. Methods: Patients were identified from operating theatre logbooks. All relevant data was obtained from a retrospective review of medical and operative records. ERI was defined as evidence of positive CSF culture. Results: 41 EVDs were inserted in a total of 30 patients during the study period. The average age was 52.9 years. 46.6% of patients were female. The average length of EVD insertion was 8.85 days. The most common reason for EVD insertion was subarachnoid haemorrhage (31.7%) followed by supratentorial tumour (24.4%). 78% of EVDs were antibiotic-impregnated. Average EVD sampling rate was 0.7. ERI rate was 1/41 (2.4%). The infection occurred in a patient who had an EVD inserted for haemorrhage secondary to an AVM which had remained in situ for 13 days. The patient subsequently developed problems with repeated shunt infections resulting in a nine-month hospital stay. Conclusions: The ERI rate in our patient cohort was 2.4%. We recommend using a strict EVD sampling protocol to minimise manipulation of EVDs and where possible to limit the length of time an EVD remains in situ . EVD-related infections can result in lengthy hospital stays and increased healthcare costs.